Elevated levels of fragmented DNA nucleosomes in native and activated lymphocytes indicate an enhanced sensitivity to apoptosis in sporadic Alzheimer’s disease: specific differences to vascular dementia - Eckert, Anne; Oster, Manfred; Zerfass, Richard; Hennerici, Michael G.; Müller, Walter E. (Dementia and geriatric cognitive disorders, 2001)
Apoptotic cell death is thought to be the most likely mechanism of cell death contributing to neurodegeneration in Alzheimer’s disease (AD). Here, we provide evidence that in sporadic AD cases the vulnerability of peripheral cells to undergo apoptosis is increased compared to non-demented elderly controls and, very importantly, to patients with subcortical vascular encephalopathy (SVE) as another, but demented control group. Quiescent ‘native’ and ‘activated’ lymphocytes from AD patients that were predisposed to commit apoptotic cell death by priming the cells with interleukin-2, are shown to accumulate apoptosing cells to a significantly higher extent in spontaneous and in oxidative stress-induced in vitro apoptosis. Our results demonstrate robust differences in cell death sensitivity between AD and vascular dementia. In none of the conditions investigated, lymphocytes from SVE patients were significantly different from non-demented controls. The comparable findings of a higher extent of apoptotic features in neurons and in peripheral blood cells of AD patients are remarkable and may suggest a rather general modulation of apoptotic mechanisms by the disease, which even can be picked up at the level of peripheral lymphocytes under specific in vitro conditions.
Gesehen am 31.03.2021